Analisis Ketersediaan Air dengan Metode F.J. Mock untuk Kebutuhan Air Bersih di DAS Borong Kabupaten Manggarai Timur - Anwar; Khaeruddin2, Dian Noorvy ; Sulistyani, Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
NTT is an area with relatively dry climatic conditions where the rainy season only lasts 3-4 months and the dry season is 8-9 months so it needs an analysis of the availability of water in each water source, one of which is the Borong watershed. The purpose of this study is to calculate how many mainstay debits are in the Borong watershed and find out the need for clean water in the area entering the Borong watershed area. There are two climatological stations that are influential in the Borong watershed, namely Stamet Ruteng and Wae Bobo / Borong. The data used has a span of time for the last 10 (ten) years, namely from 2007 - 2016 with the average rainfall of the two stations is 2132 mm / year, while the average Q99% discharge obtained is 2.258 million m3 / month . To calculate water requirements, the population data is used for 5 (five) years and projected for the next 20 (twenty) years. From the projection results, the current water demand is 0.00003 million m3 / month, while in 2037 it is 0.0011 million m3 / month. The water balance for clean water needs is currently experiencing a surplus of 2.233 million m3 / month, while in 2037 it has a surplus of 2.20 million m3 / month. Of the remaining water that will be used for the needs of irrigation water with an assumption of 1 liter / second / ha, the total irrigation area that can still be utilized is 257 ha with a minimum surplus in October is 0.002 million m3 / month. Thus it can be concluded that the water in the Borong watershed is able to meet the needs of clean water that is available and can still be used for irrigation water needs.